Effect of Heat Treatment Time on the Microstructure and Hardness of Particle ReinforcedNi - Base Alloy for Internal Combustion Engine under 1 000 ℃ - CHEN Xiao-jing, QU Jian-hua, DONG Bin (Cailiao Baohu, 2021)
In order to improve the microstructure and properties of nickel-based alloy for internal combustion engine, with selecting nickel-based powder alloy as the test material, the bars with compact microstructure were obtained by hot extrusion consolidation molding method firstly, and then the bars were processed by the thermal treatment with different time under 1 000 ℃. In addition, the microstructure and hardness were studied by means of experimental test. Results showed that the grain size uniformity of hot-pressed nickel-based alloy was poor, and the phenomenon of small grain aggregation occurred. After hot extrusion treatment, a large number of high-density dislocations and mutual accumulation appeared in the alloy, and the mechanical strength of nickel-base alloy was improved greatly after hot extrusion. When the heat treatment time reached 8 h, the size of grains continued to grow larger, but the rate of growth decreased. After 8 h of heat treatment, the grain size was further increased, but the rate was slowed down. Most of the nanoparticles were distributed in the grain and grain boundary area, with a particle size of about 36 nm. Furthermore, the hardness decreased rapidly under the condition of prolonging heat treatment time gradually. The alloy obtained stable hardness after 8 h heat treatment, while the hardness of the sample became the minimum after 96 h heat treatment.